Inhibition of the mobility of mouse lymphocyte surface immunoglobulins by locally bound concanavalin A. - Henis, Y I (1981)
Fluorescence photobleaching recovery was used to study directly and quantitatively the inhibition of the lateral mobility of surface immunoglobulins (sIg) on mouse lymphocytes by localized binding of concanavalin A (Con A) coupled to platelets. Up to a threshold occupancy of about 10% of the upper cell surface by Con A-platelets, the diffusion coefficient and mobile fraction of sIg remained as in untreated cells (5.3 X 10(-10) cm2/sec and 0.65, respectively). At higher surface occupancy, these values decreased to 8 X 10(-11) cm2/sec and 0.11. The magnitude of the effect was independent of the percentage occupancy above the threshold and of the distance from the bound Con A-platelets, indicating a cooperative and propagated phenomenon. Treatment with colchicine or cytochalasin B separately induced only partial reversal of the Con A-induced modulation. Treatment with both reversal of the Con A-induced modulation. Treatment with both drugs together was synergistic and fully reversed the mobility inhibition. The modulation was unaffected by NaN3 and 2-deoxyglucose, suggesting no dependence on metabolic energy. Con A-platelets did not affect the mobility of a lipid probe. Models for the Con A-induced modulation and the relationship between the effects of Con A on sIg mobility and patch formation are discussed.